2019
DOI: 10.2174/1381612824666181106111020
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting and Structural Insight into the Binding of Novel Plant-Derived Molecules of Leea indica as Inhibitors of BACE1

Abstract: Alzheimer disease (AD) can be considered the most common age-related neurodegenerative disorder, and also, an important cause of death in elderly patients. A number of studies found the correlation of this disease pathology with BACE1 inhibitor and it is also evident that BACE1 inhibitor can function as a very potent treatment strategy in treating AD. In the present study, we aimed to prospect for novel plant-derived BACE1 inhibitors from Leea indica and to realize the structural basis of their interactions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Moreover, other studies indicated that lupeol have neuroprotective property . It has also been reported that lupeol inhibits BACE1 with an IC 50 value of 5.12 μM …”
Section: Bace1 As a Potential Target For The Treatment Of Alzheimer'smentioning
confidence: 87%
See 4 more Smart Citations
“…Moreover, other studies indicated that lupeol have neuroprotective property . It has also been reported that lupeol inhibits BACE1 with an IC 50 value of 5.12 μM …”
Section: Bace1 As a Potential Target For The Treatment Of Alzheimer'smentioning
confidence: 87%
“…Furthermore, although both compounds formed hydrophobic interactions with Tyr71 residue at the flap region, however, none of them was able to interact with the catalytic aspartic acid residues (Asp32 and Asp228). Theoretical calculations of the PK values have shown that lupeol could cross the BBB more efficiently than ursolic acid . Moreover, other studies indicated that lupeol have neuroprotective property .…”
Section: Bace1 As a Potential Target For The Treatment Of Alzheimer'smentioning
confidence: 99%
See 3 more Smart Citations